(untitled) (Ibrahim Medical College Journal, 2008)
Cytologic diagnosis by fine needle aspiration of the prostate was compared to histological diagnosis by either core biopsy or transurethral prostatic resection in 58 patients suspected to have prostatic lesion by rectal examination.The diagnostic accuracy between cytological and histological diagnosis was 93% and the false negative rate was 3.03% for fine needle aspiration. Inadequate cytological samples occurred only in two cases. This study was conducted during the period of April 2003 to February 2004. Fine needle aspiration cytology of prostatic lesions is a recently introduced procedure in Bangladesh. Our results indicate that fine needle aspiration is an easily performed, diagnostically reliable outpatient procedure with minimal complication. Ibrahim Med. Coll. J. 2007; 1(1): 7-10 Key words : FNAC, Franzen, Papaniculaou doi: 10.3329/imcj.v1i1.2888